The role of protected areas in modulating vegetation response to climatic stressors in hyper-arid ecosystems - Ammar Abulibdeh (15785928) (2025)
Arid and semi-arid regions are increasingly vulnerable to climate variability, water scarcity, and land degradation, making vegetation health highly sensitive to environmental stressors. In this context, protected areas are a critical conservation strategy. This study assesses the effectiveness of Qatar’s three major protected areas: Al Reem, Khor Al Adaid, and Al Thakhira, established in 2006, in modulating the responsiveness of vegetation to climatic drivers. Using Landsat-derived NDVI (1990–2022), ERA5-Land climate variables, and statistical techniques (linear regression, ANOVA, Kruskal-Wallis, Tukey’s HSD, and Dunn’s test), we compared vegetation–climate coupling before (1990–2006) and after protection (2007–2022). Results show that vegetation sensitivity to climate drivers increased significantly post-protection. For example, in Al Reem, the effect of evaporation on NDVI shifted from a non-significant, 28.1 (p = 0.136) before 2006 to a significant, 18.5 (p = 0.007) after protection, while the number of precipitation events lost its prior significance (β = 3.4, p = 0.016 → p = 0.981). In Al Thakhira, temperature became a stronger positive predictor of NDVI after 2006 (β = 13.9, p = 0.003 vs. β = 6.6, p = 0.176), and precipitation accumulation turned significantly positive (β = 3.2, p = 0.043). By contrast, Khor Al Adaid exhibited weaker overall responsiveness, though post-protection NDVI became significantly associated with relative humidity (β = 0.43, p = 0.006) and dew point (β = − 1.05, p = 0.006). These results demonstrate that the establishment of protected areas in 2006 enhanced vegetation–climate coupling in hyper-arid ecosystems, particularly through improved responsiveness to moisture-related variables. Findings underscore the ecological and policy relevance of expanding conservation zoning and integrating hydrometeorological indicators into land management strategies. Other Information Published in: Journal for Nature Conservation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jnc.2025.127081